Long-term anticoagulation and selective cells adhesion surface via combination of covalent grafting and layer by layer assembly. (8th October 2019) - Li, Chaojing; Mao, Jifu; Li, Qiwei; Wang, Fujun; Jiao, Yongjie; Zhang, Ze; Guidoin, Robert; Wang, Lu
Abstract: Surface modification by long-term active component is essential for biocompatible polymers-based vascular grafts to prevent thrombus formation and reduce intimal hyperplasia. In this study, a simple approach was developed to immobilize bioactive heparin to the surface of ε -polycaprolactone (PCL) grafts through a two-step strategy combining covalent grafting and layer by layer assembly of polyelectrolytes. The performance of heparinized PCL was evaluated in vitro, including the release behavior of heparin, anticoagulation and different types of cells adhesion characteristic. A sustained-release of heparin was achieved by this immobilization strategy. Surface remaining heparin was up to 1.10 μ g cm −2 on the modified PCL after release in vitro for 30 d. Specifically, the heparinized PCL has the long-term ability to prevent adhesion of blood cells and thrombus formation, and significantly inhibit the adhesion of smooth muscle cells. The two-step strategy provides a simple and general route to incorporate heparin on PCL graft surface. The surface heparinized PCL demonstrated in this work can be a useful material platform for biodegradable vascular stent graft.